Dispersion in ventricular repolarization in the human, canine and porcine heart. Issue 1 (January 2016) - Opthof, Tobias; Janse, Michiel J.; Meijborg, Veronique M.F.; Cinca, Juan; Rosen, Michael R.; Coronel, Ruben
Abstract: Dispersion in repolarization is important for the genesis of the T wave, and for the induction of reentrant arrhtyhmias. Because the T wave differs across species our intent here is to review the epicardial, endocardial and transmural repolarization patterns contributing to repolarization in whole hearts from man, dog and pig. The major points we emphasize are: transmural repolarization time gradients are small and are directed from endocardium (early) to epicardium (late) in dog and human and from epicardium to endocardium in pig; the right ventricle tends to repolarize before the left ventricle and this difference is larger in dog than in pig; a negative relation between the activation times and the repolarization times is rare in man, and absent in dog and pig. Given the above, a large dispersion in repolarization between two myocardial areas does not lead to arrhythmias without a premature beat. Moreover, an arrhythmic substrate can be identified by a metric composed of activation times and repolarization times, the reentry vulnerability index, RVI.